Strategies of Community Empowerment to Manage Protection Forest Sustainably - Fitta Setiajiati; Hardjanto Hardjanto; Hendrayanto Hendrayanto (Institut Pertanian Bogor (IPB University), 2017)
The Indonesian Government has empowered communities that are living adjacent to forests, but at the same time, protection forests are highly encroached by the local community. In response, our study aims at formulating strategies of community empowerment in protection forest management. Data collection through participatory observation, questionnaire surveys, interviews, and focused group discussions were conducted in the surrounding communities of protected forest areas in Sumbawa District, Indonesia. A combination of descriptive, participatory, and explorative approaches were used for data analysis. The knowledge of local communities on protection forest conservation was found to be on an average level, while their attitudes towards conservation were assessed as being on a higher level. Community empowerment programs implemented by the government were shown to have no significant effect on knowledge improvement, but they were more effective in changing the community's attitudes regarding protection forest management. Local communities were shown to be willing to conduct conservation activities as well as looking for cash income. Therefore, our study suggested that community empowerment programs should link forest conservation with income opportunities for local people, such as implementing conservation agriculture (e.g. agroforestry), partnerships in the production and sale of non-timber forest products, and be conducting clearly reward and punishment for communities.